2013
DOI: 10.1186/1471-2164-14-164
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and functional study of lipid metabolic genes in Caenorhabditis elegans

Abstract: BackgroundAnimal models are indispensable to understand the lipid metabolism and lipid metabolic diseases. Over the last decade, the nematode Caenorhabditis elegans has become a popular animal model for exploring the regulation of lipid metabolism, obesity, and obese-related diseases. However, the genomic and functional conservation of lipid metabolism from C. elegans to humans remains unknown. In the present study, we systematically analyzed genes involved in lipid metabolism in the C. elegans genome using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 90 publications
(78 reference statements)
5
76
1
Order By: Relevance
“…The C. elegans genome contains 22 genes known to encode acyl-CoA synthetase/fatty acid transporter (Zhang et al 2013), of which ACS-20 is required for incorporation of exogenous very long chain fatty acids into sphingomyelin (Kage-Nakadai et al 2010). While ACS-22 may functionally overlap with ACS-20 (Kage-Nakadai et al 2010), we found that only ACS-20 is required for the increased fat accumulation under iron overload, suggesting that ACS-20, like SGK-1, regulates lipid hemostasis under iron overload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The C. elegans genome contains 22 genes known to encode acyl-CoA synthetase/fatty acid transporter (Zhang et al 2013), of which ACS-20 is required for incorporation of exogenous very long chain fatty acids into sphingomyelin (Kage-Nakadai et al 2010). While ACS-22 may functionally overlap with ACS-20 (Kage-Nakadai et al 2010), we found that only ACS-20 is required for the increased fat accumulation under iron overload, suggesting that ACS-20, like SGK-1, regulates lipid hemostasis under iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, dietary lipids are taken up by cells by lipid transporters. The C. elegans genome contains a number of genes with homology to known lipid transporters that may display similar or distinct functions (Zhang et al 2013). We tested several strains with mutations in putative lipid transporter genes including the acs-20(tm3232) strain, which carries a deletion in the acs-20 gene that encodes an ortholog of mammalian fatty acid transport proteins FATP1/4 (Kage-Nakadai et al 2010) (www.wormbase.org).…”
Section: The Fatty Acid Transporter Acs-20 Is Required For Ironinducementioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans stores fat in intestinal and hypodermal LDs (Hellerer et al 2007). Both mutant analysis and RNA interference (RNAi) screens in C. elegans have revealed evolutionarily conserved genes linked to LD size (Zhang et al 2013). Most of these genes encode proteins that participate in lipogenesis, ß-oxidation, phospholipid synthesis and binding, and the intracellular transport of fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, several genes involved in the synthesis, storage, and utilization of lipids have been identified in Caenorhabditis elegans and shown to be highly conserved (Zhang et al 2013). C. elegans stores fat in intestinal and hypodermal LDs (Hellerer et al 2007).…”
Section: Introductionmentioning
confidence: 99%